Empowering the lifelong learner: A systematic review of heutagogical approaches in language learning - Kamrozzaman, Nurul Aisyah; Jie, Amy Liew Xiu (Edelweiss Applied Science and Technology, 2025)
In light of the growing necessity for lifelong learning beyond formal education, this review aims to synthesize empirical evidence on the application and outcomes of heutagogy, or self-determined learning, within language acquisition contexts. The objective is to assess its efficacy and identify key factors for successful implementation. This study employed a systematic review methodology, rigorously following the PRISMA guidelines. A comprehensive search and screening process was conducted, resulting in the final analysis of 33 relevant studies that investigated heutagogical principles in language learning. The analysis reveals that heutagogy is highly effective in fostering essential skills for lifelong learners, including increased autonomy, enhanced metacognitive awareness, and improved language proficiency, often through strategies like negotiated curricula. However, significant challenges were identified, such as varying levels of learner readiness and the exacerbating effect of the digital divide, indicating that success is not universal. Heutagogy presents a robust framework for empowering lifelong language learners. Nevertheless, its effectiveness is contingent upon careful contextualization, requiring culturally responsive adaptation and supportive technological ecosystems to bridge implementation gaps. The findings provide a critical evidence base for educators and policymakers, particularly in the Malaysian context, to design learner-centric language programs. This review underscores the need for professional development on heutagogical principles and highlights the necessity for further localized research to translate theory effectively into practice.